Effects of respiratory muscle training on lung function in adolescents with overweight and obesity - María-Francisca Parra-vera; Yeny Concha-Cisternas; Joaquín Salazar-Méndez; Pablo Valdes-Badilla; Eduardo Guzman Muñoz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The prevalence of overweight and obesity in adolescents has reached alarming rates globally, with significant implications for health, including compromised lung function. This study investigated the effects of progressive respiratory muscle training (RMT) on lung function in overweight and obese adolescents. A quasi-experimental design was employed with 28 participants, randomly assigned to RMT or control groups. Lung function was assessed using spirometry and pymometry before and after an 8-week intervention. Results revealed significant improvements in spirometry variables (FEV1, FVC, PEF, FEF25, FEF50, FEF75, FEF25-75) and pymometry variables (MIP, MEP) in the RMT group compared to controls. However, no significant changes were observed in the restrictive ventilatory pattern. The findings suggest that isolated RMT enhances lung function and respiratory muscle strength in overweight and obese adolescents. Future interventions should consider combining RMT with strategies to reduce BMI for comprehensive improvements in respiratory health in this population.